Prevalence of Skeletal Anteroposterior Malocclusions in Skeletally Mature Patients in Puerto Rico: A Pilot Study - Rivera, Laura; Elías-Boneta, Augusto R.; García Rodríguez, Omar; Buxó-Martinez, Carmen J.; Oliva, Jazmin; Rivas-Tumanyan, Sona (Puerto Rico Health Sciences Journal, 2025)
Objective: To estimate the prevalence of skeletal anteroposterior malocclusions and their associated components in orthodontic patients living in Puerto Rico. Methods: A cross-sectional study was conducted with 50 normodivergent patients (cervical vertebral maturation stages 4–6) from the Orthodontic Graduate Program (2012–2014) of the University of Puerto Rico, Medical Sciences Campus. A calibrated examiner obtained five measurements (Frankfort Horizontal–Sella–Nasion, Sella–Nasion–Gonion–Gnathion, Sella–Nasion–A point, Sella–Nasion–B point, and A point–Nasion–B point) from patients’ initial cephalometric x-rays using Dolphin Imaging software, version 11.7, to determine the presence and distribution of skeletal jaw discrepancies. Sex-based differences were explored using the Mann-Whitney and Fisher’s exact tests. P < .05 was considered statistically significant. Results: The prevalence of skeletal discrepancies was 78%. The most common skeletal malocclusion was Class II (54%), followed by Class I (34%) and Class III (12%). Class II malocclusions were associated with maxillary prognathism (59%), whereas Class III malocclusions were attributed to mandibular prognathism (83%). Most Class I patients did not present a discrepancy (65%); however, we observed bimaxillary prognathism in 24% of Class I patients, and a low position of Sella was detected in 54% of the sample. No significant sex-based differences were observed in the five cephalometric x-ray measurements (P > .05). Conclusion: A high percentage of patients presented with a skeletal malocclusion. Class II skeletal malocclusions due to maxillary prognathism predominated; no sex-based differences were found for skeletal jaw discrepancies; a low Sella position was frequently observed.